الحاجة إلى المعرفة وعلاقتها بحل المشكلات لدى طلبة معهد الفنون الجميلة (Journal Of Educational and Psychological Researches, 2015)
the aims of the research have been determined as :                                   1- Need for cognation according to the students of   the Fine Arts Institute. 2-  Problem-solving tothe students of the  Fine Arts Institute.3- The correlation between the needfor cognition and Problem-solving manner. according to the students of   the Fine Arts Institute.4_- Indication of differences in the manner of problem-solving,and need for cognition depending upon the variables of person, gender(males, females).The research sample consisted of (400) students from institutes of Fine Arts students,were selected randomly-styleclass of malesand females, out of academic specialitest. The researcher had been used in the research two tools: First one is Problem-Solving Measure; the researcher built it, and after extracting its psychometric features, the scale finally became composed of (53) items.Where as the second tool is the Need-for-Cognition Scale according to Cacioppo & Petty theory, and extracted its psychometric features which consisted of (18) items. The following statistical methods were employed: Chi-Squared test , the second test for two separates samples, Pearson  Correlation Coefficient, Cronbach’s Alpha formula, Strength of Excellence formula, Difficulty of Period Formula, the wrong alternative activity formula,  Dual Dot Correlation Coefficient, Kuder-Richardson formula, Spearman Corrective formula,  One Sample Dual Test, Interaction-based Variance Dual Analysis,  Scheffe’s Test for Post Comparisons